SACROILIAC JOINT SYNDROME – DESCRIPTION OF PAIN ETIOLOGY - Krawczyk-Wasielewska, Agnieszka; Skorupska, Elżbieta; Mojs, Ewa; Malak, Roksana; Keczmer, Przemysław; Kalmus, Piotr; Samborski, Włodzimierz (European Scientific Journal, ESJ, 2014)
Numerous clinical studies have supported the thesis that sacroiliac (SI) joints constitute one of the causes of spinal pain radiating to the lower limb. The pathology of SI joint has been variously defined. The majority of definitions refer to the joint structure as the potential source of pain.As far as the etiology of SI joint dysfunction is concerned, it has not been disambiguated yet.Among the main causative factors, injuries and strains of the structures surrounding the joint are noted.Joint pathology usually manifests itself by pain occurring within the area of the joint.The causes of pain may be divided into two categories: intra-articular and extra-articular.Pain caused by the SI joint may be nociceptive or neural in nature, whereaspain pattern characteristic of the joint correlates with its innervation (S2 dorsal rami) and is consistent with the localisation of radicular pain to a large extent.